Hemolytic Uremic Syndrome: Toxins, Vessels, and Inflammation - Cheung, Victoria; Trachtman, Howard (Frontiers in Medicine, 2014)
Hemolytic uremic syndrome (HUS) is characterized by thrombotic microangiopathy of the glomerular microcirculation and other vascular beds. Its defining clinical phenotype is acute kidney injury, microangiopathic anemia, and thrombocytopenia. There are many etiologies of HUS including infection by Shiga toxin (Stx)-producing bacterial strains, medications, viral infections, malignancy, and mutations of genes coding for proteins involved in the alternative pathway of complement. In the aggregate, although HUS is a rare disease, it is one of the most common causes of acute kidney injury in previously healthy children and accounts for a sizable number of pediatric and adult patients who progress to end stage kidney disease. There has been great progress over the past 20 years in understanding the pathophysiology of HUS and its related disorders. There has been intense focus on vascular injury in HUS as the major mechanism of disease and target for effective therapies for this acute illness. In all forms of HUS, there is evidence of both systemic and intra-glomerular inflammation and perturbations in the immune system. Renewed investigation into these aspects of HUS may prove helpful in developing new interventions that can attenuate glomerular and tubular injury and improve clinical outcomes in patients with HUS